Recent developments of c‐Met as a therapeutic target in hepatocellular carcinoma - Bouattour, Mohamed (Hepatology, 2018)
Aberrant c‐Met activity has been implicated in the development of hepatocellular carcinoma (HCC), suggesting that c‐Met inhibition may have therapeutic potential. However, clinical trials of nonselective kinase inhibitors with c‐Met activity (tivantinib, cabozantinib, foretinib, and golvatinib) in patients with HCC have failed so far to demonstrate significant efficacy. This lack of observed efficacy is likely due to several factors, including trial design, lack of patient selection according to tumor c‐Met status, and the prevalent off‐target activity of these agents, which may indicate that c‐Met inhibition is incomplete. In contrast, selective c‐Met inhibitors (tepotinib, capmatinib) can be dosed at a level predicted to achieve complete inhibition of tumor c‐Met activity. Moreover, results from early trials can be used to optimize the design of clinical trials of these agents. Preliminary results suggest that selective c‐Met inhibitors have antitumor activity in HCC, with acceptable safety and tolerability in patients with Child‐Pugh A liver function. Ongoing trials have been designed to assess the efficacy and safety of selective c‐Met inhibition compared with standard therapy in patients with HCC that were selected based on tumor c‐Met status. Thus, c‐Met inhibition continues to be an active area of research in HCC, with well‐designed trials in progress to investigate the benefit of selective c‐Met inhibitors. (Hepatology 2018;67:1132–1149)